Online and Collaborative Learning Design model based on IMS-LD to Stimulate Collaborative Learning in E-learning Environments - MHOUTI, Abderrahim EL; ., Mohamed ERRADI (Journal of Education and Vocational Research, 2015)
In the e-learning field, there is an urgent need for the sharing, reuse and design of online courses as learning objects. However, in the vast majority of cases, e-learning courses are built in a manner that not stimulating cooperation, interaction, and collaborative learning. The primary aim of this paper is to develop a strategy for constructing learning objects, strategy targeted at supporting instructors in designing educational contents in order to promote collaborative learning in e-learning environments. A key challenge in this work is the definition of a new method of learning design of e-learning contents to stimulate collaborative learning. In addition, we introduce a general model of online and collaborative learning design. Model is based on the methods of instructional design and Educational Modeling Languages, particularly the IMS-LD specification. Firstly, the paper presents the online and collaborative design process of a content based on a life cycle adapted. Then, the paper describes the steps of the modeling process of content. Finally, the paper exposes the adopted technical choices and a first prototype is set up to provide a subjective evaluation of the new framework.